Expertise‐based randomized clinical trial of laparoscopic versus small‐incision open cholecystectomy (Br J Surg 2013; 100: 886–894). (February 2014) - Naraynsingh, V.; Singh, Y.; Dan, D.; Maharaj, R.
Abstract : The Editors welcome topical correspondence from readers relating to articles published in the Journal. Responses should be sent electronically via the BJS website ( www.bjs.co.uk ). All letters will be reviewed and, if approved, appear on the website. A selection of these will be edited and published in the Journal. Letters must be no more than 250 words in length .